Diseño e implementación de cabina de desinfección personal, para el ingreso a los galpones de granjas avícolas - Peláez Herrera, Juan José; Cerón Gasca, Kevyn Makey (Universidad Antonio Nariño, 2021)
The purpose of this project is to build an automated disinfection booth to mitigate the health risk to the entry of poultry farms sheds by operators, taking into account that these spaces must have a rigorous disinfection process to mitigate the risk of contracting diseases that are usually transmitted by body secretions of the operators or caretakers of the birds, particles that are mixed in the air, dust or any other mechanical means. Being a method that allows to have a control in the process a priori of the interaction with the birds, for this there is a control system of spray of disinfectant that has the national permits and does not affect the health or garments of the operators, The automation used in the processes achieves operation in the spraying process and completion of the process. It was verified by a bacterial culture analysis, giving as a result 97% efficiency in the disinfection of the operator. It is concluded that the disinfection booth achieves with the aim of minimizing the biological risk that birds have when having contact with operators who enter the sheds